Secondary Prevention and Quality of Life of Patients with Stable Coronary Heart Disease - E. D. Zharkova; Yu. V. Lukina; N. P. Kutishenko; E. T. Huseynova; N. P. Zolotareva; S. Yu. Martsevich; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. To assess the quality of life of patients with stable coronary heart disease (CHD) initially and 12 months after drug and non-drug secondary prophylaxis according to clinical guidelines.Material and methods. 73 patients (57 men, 16 women) with confirmed stable coronary artery disease were included in the study, of which 44 patients described a clinic for angina pectoris of functional class I-IV. The study included 2 patient visits: an initial treatment visit (V0) and a repeat visit after 12 months (V2). At both visits, blood pressure (BP), low-density lipoprotein cholesterol (LDL-c), quality of life (QL) were assessed using SAQ (Seattle Angina Questionnaire), drug therapy. Compliance with 5 basic principles of prevention was also assessed, which included: (1) healthy lifestyle (healthy lifestyle) (rejection of bad habits (smoking), moderate physical activity, lowcholesterol and low-carb diet); (2) normalization of body weight; (3) optimal drug therapy (the frequency of taking medications was evaluated using the original questionnaire); (4) achievement of target values of LDL-c in the entire group; (5) blood pressure in hypertensive patients. During V0, if necessary, drug therapy was adjusted in accordance with clinical recommendations. During V2, 57 patients (47 men and 10 women) were examined. The response was 80.8%.Results. After 12 months of follow-up, a statistically significant improvement in exercise tolerance (p=0.003), angina stability index (p=0.045) and the frequency of stress angina attacks (p=0.003) was noted when assessing the median of QL indicators. After 12 months of follow-up, 59% of patients used optimal drug therapy, including 4 drugs according to clinical guidelines. A healthy lifestyle (regular physical activity and smoking cessation) was achieved in 20.4% after 12 months of follow-up, the target level of LDL-c ˂ 1.8 mmol/L was achieved in 44.5% of patients, and the target blood pressure was achieved in 74,6%. The achievement of all 5 principles of secondary prevention of coronary heart disease according to the results of the work carried out by the visit after 12 months of follow-up was revealed only in 7% of patients (4 patients), and the implementation of 4 principles of prevention was noted in a quarter of patients from the group (24.5%, n=14).Conclusions. With drug and non-drug secondary prevention of coronary heart disease in patients with stable CHD after a year of follow-up, a statistically significant increase in QL indicators was noted due to increased exercise tolerance and a decrease in the frequency of angina attacks. Nevertheless, the basic principles of prevention were fully implemented only in 7% of patients.